A Place for All People: Louise Nevelson’s Chapel of the Good Shepherd - Watson, Caitlin Turski (Religions, 2022)
In 1973, a church and a bank joined forces to reimagine an entire block of Midtown Manhattan. The church was St. Peter’s, and the bank was First National City Corporation, or Citicorp. The Citicorp Center, now owned jointly by St. Peter’s and the developer Boston Properties, remains an important nexus in Midtown. The following case study considers both the limitations of the site’s privately owned public spaces and how the Nevelson Chapel, a permanent public art installation located within St. Peter’s Church, operates as a counter-hegemonic form of privately owned public space—the sacred public space.